Informal out-of-pocket payments experience and individuals' willingness-to-pay for healthcare services in Greece. Issue 6 (June 2021) - Giannouchos, Theodoros V.; Ukert, Benjamin; Vozikis, Athanassios; Steletou, Evangelia; Souliotis, Kyriakos
Highlights: About 80% of respondents were willing to pay for healthcare services. More than half were involved in an informal healthcare related transaction. Higher informal payments were associated with increased willingness-to-pay for healthcare services. Support towards legalizing informal payments was also associated with increased willingness-to-pay. Abstract: Background: Informal out-of-pocket payments to healthcare providers are not uncommon in the Greek health system. We explore individuals' willingness-to-pay (WTP) to secure zero out-of-pocket full coverage for healthcare services and medications and we estimate the impact of past informal payments and individuals' opinion about the legalization of informal payments on WTP. Methods: We conducted a survey of 2841 participants from November 2016 to February 2017. We obtained information on WTP using the contingent valuation method. A two-part regression model was used to estimate the association between WTP, informal payments, and respondents' opinion about legalizing such payments. Results: About 80% of the respondents were willing to pay an average of €95 per month to obtain free access to full healthcare coverage and medications. About 65% of the respondents were involved in an informal payment at least once during the past four months with an average payment of €247. Higher informal payments and supportive opinions towards the legalization of informal payments increased the likelihood of WTP and were also positively associated with increased WTP amounts overall ( p < 0.001). Conclusions: This survey reveals that individuals' WTP is critically affected by previous experiences and attitudes towards informal payments. Our results imply that the potential introduction of official fees might not suffice to limit informal payments and suggest the need for stricter regulatory policies.